PENGARUH MOTIVASI BELAJAR INTRINSIK DAN EKSTRINSIK TERHADAP HASIL BELAJAR MATA PELAJARAN MEMELIHARA SISTEM BAHAN BAKAR BENSIN SISWA KELAS XI SMK TAMANSISWA NANGGULAN TAHUN PELAJARAN 2015/2016 - Muh Juandi Arif Baitullah; Pairun Roniwijaya (Universitas Sarjanawiyata Tamansiswa, 2016)
The purpose of this study was to determine: (1) the effect of intrinsic learning motivation towards the outcomes of the study in ‘maintaining gasoline fuel system’ learning subject; (2) the effect of extrinsic learning motivation towards the outcomes of the study in ‘maintaining gasoline fuel system’ learning subject; and (3) the influence of intrinsic and extrinsic learning motivation towards the outcomes of the study in ‘ maintaining gasoline fuel system’ subject in class xi of smk tamansiswa nanggulan academic year 2015/2016. The type of the research is ex-post facto. The population of the study was all students of class XI in Light Vehicle Engineering study Program of SMK Tamansiswa Nanggulan, they were 57 students which spread in over three classes in which at the same time became the research sample. In data collection Methods, the study was using questionnaires and documentation. In Data analysis technique, the researcher used descriptive analysis, first and second hypothesis testing were using partial correlation test and the third hypothesis testing was using multiple regression of two predictor which preceded with test of analysis requirements, which is test for normality, linearity and multicollinearity. The results shows that: (1) there is a positive and significant influence between intrinsic learning motivation towards the outcomes of the study in ‘maintain gasoline fuel system’ learning subject on class xi of smk tamansiswa nanggulan lesson year 2015/2016 with correlation coefficient ‘rhitung’ of 0.456 and the value of significant level of 0.000. <0.05. (2) there is a positive and significant influence between extrinsic learning motivation towards the outcomes of the study in ‘maintain gasoline fuel system’ learning subject on class xi of smk tamansiswa nanggulan lesson year 2015/2016 with correlation coefficient ‘rhitung’ of 0.339 and the value of significant level of 0.011. <0.05.(3) there is a positive and significant influence between extrinsic and intrinsic learning motivation simultaneously towards the results of study on maintaining gasoline fuel system subject in class XI, students of SMK Tamansiswa Nanggulan Academic Year 2015/2016 with value of ‘Fhitung’ = 12.572 with p value (significance) of 0.000 <0.05.